Inherited thrombocytopenias - Balduini, C. L.; Pecci, A.; Noris, P. (Hämostaseologie, 2012)
The chapter of inherited thrombocytopenias has expanded greatly over the last decade and many “new” forms deriving from mutations in “new” genes have been identified. Nevertheless, nearly half of patients remain without a definite diagnosis because their illnesses have not yet been described. The diagnostic approach to these diseases can still take advantage of the algorithm proposed by the Italian Platelet Study Group in 2003, although an update is required to include the recently described disorders. So far, transfusions of platelet concentrates have represented the main tool for preventing or treating bleedings, while haematopoietic stem cell transplantation has been reserved for patients with very severe forms. However, recent disclosure that an oral thrombopoietin mimetic is effective in increasing platelet count in patients with MYH9-related thrombocytopenia opened new therapeutic perspectives.This review summarizes the general aspects of inherited thrombocytopenias and describes in more detail MYH9-related diseases (encompassing four thrombocytopenias previously recognized as separate diseases) and the recently described ANKRD26-related thrombocytopenia, which are among the most frequent forms of inherited thrombocytopenia.
Keywords: Inherited thrombocytopenias; MYH9-related disease; ANKRD26-related thrombocytopenia; bleeding disorders